Electron--photon shower distribution function : tables for lead, copper, and air absorbers - Messel, H. (Harry), 1922-; Crawford, D. F. (Pergamon Press, 1970)
Electron-Photon Shower Distribution Function: Tables for Lead, Copper and Air Absorbers presents numerical results of the electron-photon shower distribution function for lead, copper, and air absorbers. Electron or photon interactions, including Compton scattering, elastic Coulomb scattering, and the photo-electric effect, are taken into account in the calculations. This book consists of four chapters and begins with a review of both theoretical and experimental work aimed at deducing the characteristics of the cascade produced from the propagation of high energy electrons and photons through.